The power of the oath : Mau Mau nationalism in Kenya, 1952-1960 - Mwanzia Koster, Mickie (Rochester studies in African history and the diaspora, 2016)
Opens a fresh conversation on the study of the Mau Mau rebellion and Kenyan history by arguing that Mau Mau was a nationalist movement rather than a Kikuyu war.--